Learning to hear again with alternating cochlear frequency allocations - van Hoof, Marc; Lambriks, Lars; van der Heijden, Kiki; Debruyne, Joke; Devocht, Elke; George, Erwin (Scientific reports, 2025)
Traditionally, the place-pitch ‘tonotopically’ organized auditory neural pathway was considered to be hard-wired. Cochlear implants restore hearing by arbitrarily mapping frequency-amplitude information. This study shows that recipients, after a long period of sound deprivation, preserve a level of auditory plasticity, enabling them to swiftly and concurrently learn speech understanding with two alternating, distinct frequency maps. During rehabilitation, subjects switched maps randomly on a daily basis, serving as their own control. After stating their preference, on average, subjects maintained their hearing performance with the non-preferred, legacy map over time. In addition, subjects continued to learn and improve with their map of preference. Being able to train and process the auditory information from two maps did not seem to be a competition over neural resources, such as would be the case in a typical zero-sum game. This shows a new level of flexibility in learning and long-term adaptation of the auditory system. Practically, the required novel study design halves the sample size while mitigating order effects associated with neural plasticity, benefitting sensory-oriented trials.